PELATIHAN PERANGKAT LUNAK DESAIN KAPAL SEBAGAI INISIASI PENDIDIKAN MICROCREDENTIAL BAGI MASYARAKAT - Satoto, Sapto Wiratno; Handayani, Rita; Aisyi, Rahadatul; Susmana, Haris; Febrina, Laila; Regie, Muhammad; Putri, Dina Indriana (Pusat Penelitian dan Pengabdian Masyarakat, 2024)
The high demand for drafters provides new opportunities in the world of education. Many prospective students who do not pass the educational entrance selection try to find a credible institution to accommodate the needs of a competency training institution. Batam State Polytechnic is trying to take a role by providing microcredential classes which have a skills certification output for its students. This program was tried by carrying out community service activities as a form of initiation of microcredential class activities. The service method is implemented using; direct meetings / via zoom meetings, students will be given guidance to complete assignments and carry out practical work on campus. It is hoped that this service with the theme of drawing using a computer, which is carried out online and offline, will bring benefits to students. Basic K3 is also provided as a form of commitment to prioritizing safety at work. The activity output obtained includes: increasing students' skills and knowledge, participants also know more about Polibatam as a vocational campus in Batam and produce additional output in the form of learning modules, videos and posters. The training also received a positive and good response from students so that it might then be developed and continued again.